Numerical simulation of size effects of gas explosions in spherical vessels. (August 2017) - Yan, Chen; Wang, Zhirong; Liu, Kai; Zuo, Qingqing; Zhen, Yaya; Zhang, Shangfeng
To study the law of sizes on gas explosions, numerical simulations of methane–air mixture explosions in spherical vessels were performed. The law of sizes on gas explosions is studied using FLUENT simulations with thek − ε two-equation turbulent model, the eddy-dissipation-concept model, thermal dissipation at a wall boundary, the P1 model, and the SIMPLE algorithm. The experimental results suggest that under an adiabatic condition without energy loss, the maximum explosion pressures in different spherical vessels are all 0.82 MPa, and the effect on the explosion intensity in spherical vessels is small. Under the condition of heat dissipation at the wall boundary, the maximum explosion pressure increases with volume of the spherical vessel. However, the explosion intensity in this condition is lower than that in adiabatic condition. Also, the size effect is not obvious. The size effect on the explosion intensity is significant under the combined effects of heat dissipation at the wall boundary and thermal radiation, where the maximum explosion pressure increases with volume of spherical vessels. On the contrary, the maximum pressure rising rate decreases with the volume of the spherical vessels; this rule coincides with the "cube" law. The studies on the size effects of methane–air mixture explosions in a spherical vessel provide an important reference for establishing a model system that can be used to test and design industrial vessels.